please guys answer this question please please guys please.........
Attachments:
![](https://hi-static.z-dn.net/files/d9f/49f95e0868533f897f96af233166a52d.jpg)
Answers
Answered by
6
AnswEr :
Given Expression,
Let x = cos(y)
We know that,
cos2∅ = cos²∅ - sin²∅
Therefore,
cos2∅ = 2cos²∅ - 1 or, 1 - 2sin²∅
Implies,
- 1 - cos2∅ = 2sin²∅
- 1 + cos2∅ = 2cos²∅
Now,
When x = cos(y), y would be arccos(x)
Thus,
Similar questions
Social Sciences,
5 months ago
Computer Science,
5 months ago
Hindi,
5 months ago
Math,
11 months ago
Science,
11 months ago
Physics,
1 year ago
Math,
1 year ago